Прогностичка вредност серума LXA4, MK и CXCL16 за бубрежно оштећење код деце са алергијском пурпуром: Серум ЛХА4, МК и ЦХЦЛ16 за бубрежно оштећење код алергијске пурпура - Xia, Ziwei; Cheng, Zhenfeng; Yuan, Xingrun; Xing, Shasha (Journal of Medical Biochemistry, 2025)
Objective To explore the predictive value of the combined application of serum intermediate factor (MK), lipoxin A4(LXA4), and CXC chemokine ligand 16(CXCL16) for renal damage in children with henoch-Schonlein purpura (HSP).Methods 117 children with HSP who were admitted to our hospital between January 2021 and December 2024 were selected for the HSP group. After treatment, they were followed up for 6 months, and the occurrence of renal damage was statistically analyzed. The control group consisted of an additional 59 voluntarily enrolled youngsters who received health examinations throughout the same time frame. The levels of serum MK, LXA4, and CXCL16 in the two groups of research patients were determined using an enzyme-linked immunosorbent assay, and clinical data from children with HSP were gathered.  The factors that contribute to renal damage in children with HSP were investigated using both univariate and multivariate logistic regression. Serum MK, LXA4, and CXCL16 levels were analyzed for their predictive value of renal impairment in children with HSP using a receiver operating characteristic (ROC) curve.Results Compared with the control group, the levels of serum MK, LXA4 and CXCL16 in the HSP group were all increased (P